O devir-docência das "pessoas grandes", agenciado pelos devires-menores do povo criança - Paoliello, Juliana (2016)
This work is an invitation to the "adult living" teachers that, meeting their becomingchild, dwell the AiónCMEI-Territory and inquiry educative practices that still tends to prescription, bureaucratization and clichés, that question the insistence in a schooling education to children. In the Philosophies of Difference, this study pursues concepts to move the thought, betting on the children's enunciation as a possible to enhance teacher education processes in a minor-education. Taking Deleuze and Guattari in their relation with Spinoza for major theoretical intercessors, this writing also composes with writers from the Curriculum and Everyday Life studies (CERTEAU; ALVES; CARVALHO; FERRAÇO; GARCIA; OLIVEIRA) as well as with contributors from the childhood studies (CORAZZA; GALLO; KOHAN), from the experience studies (LARROSA) and from the invention studies (KASTRUP). The research slides and strengthen itself once it encounter the fabulation function with Pequeno Príncipe and Rosa, its conceptual personae, tracing intensives maps with the (non)methodintervention of the cartography in composition with the everyday life studies. At last, as objective-results, it cartographs lines that may be clues to teaching practices committed to occupy the gaps among chaos and to affirm the life in the AiónCMEITerritory as a possible to a minor-education; lines that are only thinkable if traced with the enunciation of children-folk.